Climate change vulnerability of the Afrotemperate flora on Africa’s tropical sky islands - Elvira Castillo-Almansa; Rubén G. Mateo; Mercè Galbany-Casals; Carme Blanco-Gavaldà; Lucía D. Moreyra; Cristina Roquet; Christian Brochmann; Abel Gizaw; Desalegn Chala; Alfonso Susanna; Juan A. Calleja (Biodiversity and Conservation, 2026)
Climate change poses a significant threat to the Afrotemperate flora of the Eastern Afromontane Biodiversity Hotspot, particularly to species confined to high-elevation ecosystems such as those found on the African sky islands. This study evaluates the vulnerability of tropical Afroalpine and Afromontane Helichrysum taxa (Compositae) by assessing their climatic niches and predicting future shifts in distribution, range fragmentation, and altitudinal limits under climate change scenarios. Occurrence records for 14 taxa (eight Afroalpine and six Afromontane) were obtained from recent field campaigns, biodiversity databases and herbaria. Ensemble ecological niche models were developed combining Generalized Linear Models, Generalized Boosting Models, and Random Forest. Taxon-specific bioclimatic variables were selected after correlation analyses. The models were calibrated using current climate data and projected using the PSL-CM6A-LR and MRI-ESM2.0 climate models with both low- and high-emission scenarios. The results show that most Afrotemperate taxa currently occupy only a portion of their climatically suitable habitat, often in geographically distant areas. Future projections indicate significant range contractions and increased fragmentation. Afroalpine taxa could lose 50–66% of their suitable habitat, while Afromontane taxa could decline by 53–79%. Suitable areas were estimated to shift upwards in elevation, with limited potential for colonization of new areas, and with no significant latitudinal or longitudinal shifts. These findings represent the first continental-scale assessment of the impact of climate change on the Afrotemperate flora using ecological niche modelling. The projected climate-induced range losses and increased habitat fragmentation, in particular combined with increasing anthropogenic pressure in this region, highlight the urgent need for targeted conservation actions.